Makna Poster Pemilihan Umum 2014 (Pengamatan di Kota Kupang, Provinsi Nusa Tenggara Timur) - Wilson M.A Therik (Yayasan Bina Darma, 2015)
This paper goes from the author's experience as Chairman of the Election Supervisory Committee (Panwaslu) of Kupang for the supervision of the elections of the head of Nusa Tenggara Timur Region by 2013 and the supervision of legislative elections by 2014. The meaning of the props in Indonesian legislative election campaign (especially poster) is rarely done by researchers of the election in Indonesia. Suwonso and Kutut did the research about the meaning of the election posters of 1982 in Central Java (1987), the author also did the same observations on legislative elections 2009 in Nusa Tenggara Timur (NTT). This research was conducted in Kupang, the capital city of NTT province which became the barometer of success for elections in NTT. Similar studies are expected in the future to be a recollection of history for the constituents to choose the representatives wisely, not only because of the promises they made in the props.Keywords: Legislative Election, Politic Campaign, Poster.